Villains or victims? An ethnography of Afghan maternity staff and the challenge of high quality respectful care - Rachel Arnold; Edwin van Teijlingen; Kath Ryan; Immy Holloway (BMC, 2019)
Abstract Background Healthcare providers are the vital link between evidence-based policies and women receiving high quality maternity care. Explanations for suboptimal care often include poor working conditions for staff and a lack of essential supplies. Other explanations suggest that doctors, midwives and care assistants might lack essential skills or be unaware of the rights of the women for whom they care. This ethnography examined the everyday lives of maternal healthcare providers working in a tertiary maternity hospital in Kabul, Afghanistan between 2010 and 2012. The aim was to understand their notions of care, varying levels of commitment, and the obstacles and dilemmas that affected standards. Methods The culture of care was explored through six weeks of observation, 41 background interviews, 23 semi-structured interviews with doctors, midwives and care assistants. Focus groups were held with two diverse groups of women in community settings to understand their experiences and desires regarding care in maternity hospitals. Data were analysed thematically. Results Women related many instances of neglect, verbal abuse and demands for bribes from staff. Doctors and midwives concurred that they did not provide care as they had been taught and blamed the workload, lack of a shift system, insufficient supplies and inadequate support from management. Closer inspection revealed a complex reality where care was impeded by low levels of supplies and medicines but theft reduced them further; where staff were unfairly blamed by management but others flouted rules with impunity; and where motivated staff tried hard to work well but, when overwhelmed with the workload, admitted that they lost patience and shouted at women in childbirth. In addition there were extreme examples of both abusive and vulnerable staff. Conclusions Providing respectful quality maternity care for women in Afghanistan requires multifaceted initiatives because the factors leading to suboptimal care or mistreatment are complex and interrelated. Standards need enforcing and abusive practices confronting to provide a supportive, facilitating environment for both staff and childbearing women. Polarized perspectives such as 'villain' or 'victim' are unhelpful as they exclude the complex realities of human behaviour and consequently limit the scope of problem solving.